Principles of economics - Melvin, Michael 1948-; Boyes, William J. (South-Western Cengage Learning, 2013)
Discover the latest thinking of today's economists on important microeconomic and macroeconomic phenomena while developing with a solid global understanding of basic economic principles with Boyes/Melvin's popular PRINCIPLES OF ECONOMICS, 9E, International Edition. A reader-friendly writing style, carefully integrated learning features, and emphasis on global economics clearly illustrate the connections between key economic principles and today's actual business practices.This edition's updates, timely revisions and memorable examples ensure readers are familiar with the latest economic statistics and developments. Revised microeconomics materials emphasize the fundamentals and practical application of current events, while new macroeconomics coverage highlights the recent financial crisis and its global implications. Readers find the understanding of economic concepts and applications they need for career and business success throughout the world